2021
DOI: 10.1007/s42452-021-04303-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cutting Parameters Affecting Surface Roughness in Turning of Inconel 625 Superalloy by Cryogenically Treated Tungsten Carbide Inserts

Abstract: This work focuses on developing the mathematical model of surface roughness (Ra) in the turning of Inconel 625 superalloy with cryogenically treated tungsten carbide inserts. The influence of cryogenic treated on the microstructure and hardness of tungsten carbide tools was also investigated for the as-received inserts and deep cryogenic treatment at − 196 °C for 12, 24, and 36 h conditions. Turning experiments have been performed according to an orthogonal array L16 with three parameters (cutting tool, feed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…This situation in many studies has been associated with reducing friction owing to the reduction of the material yield strength by the temperature rise depending on increasing cutting speed. [43][44][45] The Ra approximately decreases 35-45% with an increase in cutting speed from 150 to 210 m/min while decreases 30-40% by cutting speed from 210 to 270 m/min in the milling experiments. However, considering all samples, it was observed that the Ra values increased depending on the increase in feed rate at all levels of cutting speed.…”
Section: Surface Roughness (Ra)mentioning
confidence: 99%
“…This situation in many studies has been associated with reducing friction owing to the reduction of the material yield strength by the temperature rise depending on increasing cutting speed. [43][44][45] The Ra approximately decreases 35-45% with an increase in cutting speed from 150 to 210 m/min while decreases 30-40% by cutting speed from 210 to 270 m/min in the milling experiments. However, considering all samples, it was observed that the Ra values increased depending on the increase in feed rate at all levels of cutting speed.…”
Section: Surface Roughness (Ra)mentioning
confidence: 99%
“…Especially with the optimization of the input parameters in machining, the costs can be reduced by saving time, energy consumption, and scrap. ere are many studies in the literature on the Taguchi method, which is an optimization technique [8][9][10]. is method reduces production and testing costs by reducing the number of trials [11].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers had developed various setups for deep and shallow cryogenic setup for various heat treatment sequences. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] A typical cryogenic setup is shown in Figure 3(b).…”
Section: Mechanismmentioning
confidence: 99%